Medicinal Plant Education in an effort to improve Public Health during the Pandemic (Neolectura, 2022)
The purpose of this activity is to increase productivity and improve public health. This activity was carried out in Harapan Jaya Village, Cibinong District, Bogor City. The COVID-19 pandemic is currently still engulfing Indonesia. The impact of the COVID-19 pandemic is saturation in society. Lack of productive activities to fill free time at home. Urban farming is one of the activities that can be done during a pandemic. Urban farming is able to provide economic, health and environmental benefits. Plants that can be planted can be in the form of food plants, medicinal plants (live pharmacies) or ornamental plants. Through this community service activity, the team assists in providing information to the community about family medicinal plants (TOGA) to the community in Harapan Jaya Village, Cibinong District, Bogor Regency. and a healthy and beautiful environment, which of course will have an impact on improving public health.